16.  Solve the equation for x:   2x+b=c Check this process:Step 1:   2x+b−b=c−b Step 2:   2x=c−b Step 3:   2x−2=c−b−2 Step 4:   x=c2−b−2 Check all of the choices that are true statements.(2 points)ResponsesThere is no error in the process.There is no error in the process.The process has an error from step 1 to step 2The process has an error from step 1 to step 2The process has an error from step 2 to step 3The process has an error from step 2 to step 3The process has an error from step 3 to step 4The process has an error from step 3 to step 4

1 answer

Let's evaluate the steps of the equation-solving process provided in order to identify any errors:

  1. Starting with the equation: \[ 2x + b = c \]

  2. Step 1: \(2x + b - b = c - b\)
    This step is correct because you simply subtracted \(b\) from both sides.

  3. Step 2: \(2x = c - b\)
    This is also correct as it simplifies correctly from Step 1.

  4. Step 3: \(2x - 2 = c - b - 2\)
    This step contains an error. The step incorrectly subtracts \(2\) from \(2x\), but it should simply leave \(2x\) alone and should not involve subtracting \(2\) at all. It should just state \(2x = c - b\) without further manipulation.

  5. Step 4: \(x = \frac{c - b - 2}{2}\)
    This step is incorrect, as it is based on the incorrect result from Step 3. The correct form after step 2 should be: \[ x = \frac{c - b}{2} \]

From this analysis, we can conclude:

  • The process has an error from Step 2 to Step 3.
  • The process has an error from Step 3 to Step 4 as it follows from the incorrect assertion in Step 3.

Thus, the true statements would be:

  • The process has an error from step 2 to step 3.
  • The process has an error from step 3 to step 4.

So you should select both of those responses as correct.

Similar Questions
  1. Solve the equation for x: 2x+b=cCheck this process: Step 1: 2x+b−b=c−b Step 2: 2x=c−b Step 3: 2x−2=c−b−2 Step 4:
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
  3. Consider the sequence of steps to solve the equation:5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 5 answers
more similar questions